Type-2 Fuzzy Control of DFIG for Wind Energy Conversion Systems - Mohamed Abdeldjabbar Kouadria; Selman Kouadria; Mohamed Amine Bouzid (ITEGAM-JETIA)
This study develops and designs a Type 2 fuzzy controller technique for application in wind turbines directly linked to the grid and incorporating variable-speed doubly fed induction generators (DFIG). Type 2 fuzzy theory is proposed with the aim of enhancing system performance. Unlike Type 1 fuzzy systems, it accommodates a wide range of uncertainties and dynamic nonlinearities that may constrain the system's operational efficiency. Type 2 fuzzy logic provides an effective approach to managing linguistic uncertainty by modeling the ambiguity and limited reliability of information, thereby reducing the overall level of uncertainty within the system. Both Type 1 Fuzzy Logic Control (T1FLC) and Type 2 Fuzzy Logic Control (T2FLC) techniques were employed in direct and indirect modes. The two control methods were developed, their performances were evaluated, and the most effective control method in terms of reference tracking and robustness was identified. This comparative analysis is derived from a series of tests performed under identical conditions during both transient and steady-state operations of the system. The simulation results demonstrate that the proposed method exhibits significant resilience to parameter variations and unstructured uncertainties.